Disturbance of Spatial Working Memory and its Neurophysiological Correlates in Alcohol Dependence - Asanidze, Tamar; Tsintsadze, Irine; Filia, Nino (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Patients with alcohol dependence have disorders of multiple cognitive functions. This leads to inability to control alcohol consumption, relapse or continued use of alcohol despite negative physical, psychological, and social consequences. Executive control refers to a group of cognitive functions that allow people to regulate independently their behavior and to choose appropriate actions depending on their long-term goals. Working memory (WM) is one of the main components of the executive control. The aim of the study was to evaluate indexes of spatial working memory in patients with alcohol dependence syndrome using the quantitative EEG method and the Corsi computer test. Methods. 50 patients diagnosed with alcohol dependence (F10.2 on MKB-10) were evaluated after detoxification. The control group consisted of 30 mentally and somatically healthy, age-matched subjects. The study of spatial working memory was performed by a Corsi computer test (Corsi Block-Tapping). 16-channel EEGs were recorded at background with open eyes and during the Corsi test. Spectral power absolute values of θ –, α – and β – rhythms were analyzed. Results. According to the Corsi test in alcohol dependence, the WM volume was markedly decreased compared to the healthy control group. Changes in EEG during the Corsi test in patients with alcohol dependence syndrome were associated with alpharhythm desynchronization in the prefrontal cortex and left temporal locus, which was not observed in the healthy control group. Decreased beta rhythm was observed in the central and parietal cortex of patients with alcohol dependence syndrome in response to a cognitive stimulus. In patients with alcohol dependence syndrome, theta power was significantly increased in the occipital cortex in response to a cognitive stimulus, and theta activity was significantly greater in the right temporal locus. Conclusion. The results of this study may serve as additional diagnostic criteria for cognitive disorders in patients with alcohol dependence syndrome.